2015
DOI: 10.1111/bcpt.12415
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Morphine on Pain-Related Brain Activation - An Experimental Functional Magnetic Resonance Imaging Study

Abstract: Knowledge about cerebral mechanisms underlying pain perception and effect of analgesic drugs is important for developing methods for diagnosis and treatment of pain. The aim was to explore altered brain activation before and after morphine treatment using functional magnetic resonance imaging recorded during experimental painful heat stimulation. Functional magnetic resonance imaging data were recorded and analysed in 20 healthy volunteers (13 men and 7 women, 24.9 AE 2.6 years) in a randomized, double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Studies have shown that these areas are not unique for nociception but also present a reflection of non-nociceptive-specific cognitive processes elicited by nociceptive stimulation 31,32. However, these areas were selected as most previous studies have shown a consistent activation during different pain stimuli and across various imaging and electrophysiological modalities 11,16,33,34. This validates the method used in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…Studies have shown that these areas are not unique for nociception but also present a reflection of non-nociceptive-specific cognitive processes elicited by nociceptive stimulation 31,32. However, these areas were selected as most previous studies have shown a consistent activation during different pain stimuli and across various imaging and electrophysiological modalities 11,16,33,34. This validates the method used in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, ACC and insula are regions well known to be important in pain processing . Increased functional connectivity between ACC and insula during rest has been demonstrated in chronic pain conditions, and in an acute pain model, we showed increased activity in ACC, insula, and thalamus in healthy volunteers, whereas morphine (mu‐opioid receptor agonist) decreased activity in insula, ACC, and inferior parietal cortex . Even in absence of painful stimulation, we demonstrated in the present study that oxycodone decreased functional connectivity in these brain regions.…”
Section: Discussionsupporting
confidence: 67%
“…For example, in preclinical studies using electrophysiological measures of neural activation produced by painful stimuli, morphine was reported to inhibit neuronal activity to pain evoked in a number of these regions including the S1, thalamus (the ventral posterolateral nucleus and the mediodorsal nucleus), and ACC (Wang et al, 2009 ). In human imaging studies, inhibitive effects of morphine on the pain-induced cortical activations were previously seen in the ACC, the insula and the inferior parietal cortex (Becerra et al, 2006 ; Hansen et al, 2015 ). To date, little data is available on the modulation of morphine on brain deactivations or on BA 10 response associated with pain.…”
Section: Discussionmentioning
confidence: 87%